Health conditions among farmworkers in the Southwest: An analysis of the National Agricultural Workers Survey - Soto, Sheila; Yoder, Aaron Meck; Nuño, Tomas; Aceves, Benjamin; Sepulveda, Refugio; Rosales, Cecilia Ballesteros (Frontiers in Public Health, 2022)
Agricultural jobs pose many challenges to the health and wellbeing of a disadvantaged population. In the Southwest region, the socioeconomic factors of living along the U.S.-Mexico border, migration patterns, lack of access to health care, low utilization of health care services, lack of health insurance, and highly demanding occupation may uniquely affect health outcomes for farmworkers. This paper presents descriptive information for professionals to improve access to care by tackling barriers afforded by the agricultural industry. The National Agricultural Worker Survey (NAWS) is an employment-based, random-sample survey of U.S. agricultural workers in six regions: East, Southeast, Midwest, Southwest, Northwest, and California. We examined farmworkers' self-reported health conditions, including asthma, diabetes, high blood pressure, other chronic conditions, or any condition by region from 2013 to 2016. We used logistic regression to determine differences in lifetime prevalence of health conditions between farmworkers in the Southwest region (n = 727) and farmworkers in other regions (n = 8,850) using weighted data. After adjusting for age, gender, income, insurance status, and English-speaking ability, the odds of high blood pressure and other condition were similar in all regions. The prevalence of diabetes was almost double in the Southwest (114.2 per 1,000 farmworkers). The odds of diabetes were 1.31 (95% CI 0.99, 1.74) times greater in the Southwest region than in the other regions. Asthma was the only condition that was lower in the Southwest (22 per 1,000 farmworkers) compared to the other regions. The odds of asthma were 0.61 (95% CI 0.36, 1.03) times lower in the Southwest region than in other regions. The results follow previous studies on the prevalence of asthma among the farmworker population and elevated probability of chronic diseases including diabetes among the Latino population in the U.S.